Anabolic-androgenic steroid and ephedrine use among sportsmen - Vardar, Erdal; Kurt, Cem (Journal of Dependence, 2004)
Objective: Anabolic-androgenic steroids (AAS) and ephedrine are used to enhance athletic performance or physical appearance among sportsmen. The use of these drugs can produce serious adverse medical and psychiatric effects. The primary purpose of the present study was to determine the rate of AAS and ephedrine containing drug use in sportsmen; and secondarily, to identify the socio-demographic features, dependence and abuse characteristics in AAS and ephedrine users.Methods: In the city of Edirne, two-hundred forty-two sportsmen at Trakya University Sport Academy and sportsmen attending private gymnasiums were included in the study. Subjects completed a self report questionnaire for socio-demographic features, drug abuse and dependence characteristics. DSM-IV research criteria of drug abuse and dependence were used to identify the characteristics of AAS and ephedrine users over the preceding year.Results: The results showed that 27 (11%) of the sportsmen had used AAS and ephedrine within the last 1 year. Of the 27 drug users, 6 of them were female and 6 of them were still using drugs at the time of the interview. One third of the users of AAS and drugs containing ephedrine met at least one DSM-IV research criteria for dependence and abuse. AAS and ephedrine use were more prevalent in wrestlers and body builders compared to other sportsmen. Withdrawal was the most frequently reported symptom and this symptom was characterized mainly by the presence of depressive moods. 77% of the drug users reported that they had begun to use these drugs at the behest of their trainers.Conclusion: AAS and ephedrine containing drugs use was shown to have become widespread among sportsmen in the city of Edirne. The use of these drugs may induce abuse and dependence problems among the sportsmen.
Keywords: Anabolic androgenic steroids; ephedrine; dependence; drug abuse